Simultaneous Free‐Radical and Addition Miniemulsion Polymerization: Effect of the Chain Transfer Agent on the Microstructure of Polyurethane‐Acrylic Pressure‐Sensitive Adhesives. Issue 1 (20th June 2012) - Lopez, Aitziber; Reyes, Yuri; Degrandi‐Contraires, Elise; Canetta, Elisabetta; Creton, Costantino; Keddie, Joseph L.; Asua, José M.
Abstract The effects of the CTA concentration on polymerization kinetics, polymer microstructure, particle morphology, and adhesive performance of waterborne hybrid PSAs prepared by simultaneous free‐radical and addition miniemulsion polymerizations are studied. The development of the microstructure is shown to differ from waterborne acrylic PSAs obtained by free‐radical polymerization because of the contribution of the addition reaction, which in turn causes marked differences in the adhesive performance of the final films. A computer simulation is developed to obtain detailed information about the microstructure of PU/acrylic hybrids and to correlate the microstructure with the final adhesive properties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>